Analysis of Lipid Metabolism, Immune Function, and Neurobehavior in Adult C57BL/6JxFVB Mice After Developmental Exposure to di (2-ethylhexyl) Phthalate - Bastos Sales, Liana; van Esterik, Joantine C. J.; Hodemaekers, Hennie M.; Lamoree, Marja H.; Hamers, Timo; van der Ven, Leo T. M.; Legler, Juliette (Frontiers in Endocrinology, 2018)
Background: Developmental exposure to di (2-ethylhexyl) phthalate (DEHP) has been implicated in the onset of metabolic syndrome later in life. Alterations in neurobehavior and immune functions are also affected by phthalate exposure and may be linked to the metabolic changes caused by developmental exposure to DEHP. Objectives: Our goal was to study the effects of developmental exposure to DEHP in the context of metabolic syndrome by integrating different parameters to assess metabolic, neurobehavioral and immune functions in one model. Methods: Female C57BL/6J mice were exposed to DEHP through the diet during gestation and lactation at doses ranging from 3.3 to 100000 µg/kg body weight/day (µkd). During a 1-year follow-up period, a wide set of metabolic parameters was assessed in the F1 offspring, including weekly body weight measurements, food consumption, physical activity, glucose homeostasis, serum lipids and endocrine profile. In addition, neurobehavioral and immune functions were assessed by sweet preference test, object recognition test, acute phase protein and cytokines production. Animals were challenged with a high fat diet (HFD) in the last 9 weeks of the study. Results: Increased free fatty acids (FFA) and, high density lipoprotein (HDL-C) were observed in serum, together with a decrease in glycated haemoglobin levels in blood of 1-year old male DEHP-exposed offspring after HFD challenge. For the most sensitive endpoint measured (FFA), a lower bound of the 90%-confidence interval for benchmark dose (BMD) at a critical effect size of 5% (BMDL) of 2160 µkd was calculated. No persistent changes in body weight or fat mass were observed. At 33000 µkd altered performance was found in the object recognition test in males and changes in interferon (IFN)γ production were observed in females. Conclusions: Developmental exposure to DEHP combined with HFD in adulthood led to changes in lipid metabolism and neurobehavior in male offspring and cytokine production in female offspring. Our findings contribute to the evidence that DEHP is a developmental dyslipidemic chemical, however more research is needed to further characterize adverse health outcomes and the mechanisms of action associated with the observed sex-specific effects.